Wireless stethoscope for auscultation of the heart and lungs in critically ill patients: A systematic review - Ismail, Suhartini; Prawira, Ricky; Johan, Andrew; Ismail, Rifky (Jurnal Ners, 2023)
Background:Examining the heart and lungs is necessary for critically ill patients, as these individuals may have abnormalities with either or both of these organs. This review systematically determined how the auscultation of the heart and lungs using a wireless stethoscope affected the results. Methods: The research design used was a systematic review following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Databases were searched using the search terms "auscultation," "critical patients," and "stethoscope wireless” and associated MeSH terms. The abstracts of the selected articles were examined independently by two researchers. A systematic search was conducted through several databases (Scopus, PubMed, JSTOR, and Springer-link), which were published from July 2012 to July 2022 .After reading the full content of the included studies, key themes and concepts were extracted and synthesized. Results: In total 142 articles were screened. Five articles met the inclusion criteria and were analyzed. The analysis revealed that wireless stethoscopes have increased sensitivity with indicators capable of diagnosing abnormal auscultation results in patients who have abnormal aucultation results on the gold standard. Three out of five studies suggested that the auscultation of the heart and lungs by wireless stethoscopes are more sensitive, while two other studies stated that wireless stethoscopes have the same sensitivity as manual acoustic stethoscopes. Conclusion: Based on this systematic review, a wireless stethoscope may be more sensitive than an acoustic one. Nevertheless, due to limited studies, a more well-controlled human study is warranted to be done.